KEGIATAN YAYASAN SETELAH BERLAKUNYA UNDANG-UNDANG NOMOR 16 TAHUN 2001 TENTANG YAYASAN DI DAERAH ISTIMEWA YOGYAKARTA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
This research is meant to examine the foundations activities, especially the ones concerning with the implementation of the adjustment of the foundations statutes and their constraints as well as their entries which are in accordance with the aims and purposes of the foundations as written in the statutes. The answers of the problems were taken from the library and field research. The library research was done by perusing primary, secondary, and tertiary law materials with documents as their instruments. The field research was conducted by distributing questionnaire to the staff of the foundations and interviewing Notaries as the resource persons. After the research was done and conclusion was taken, it was founded that